Habeas corpus in international law / Brian F. Farrell (University of Iowa). - Farrell, Brian R. (Brian Richard) (Cambridge University Press, 2017)
Habeas Corpus in International Law is the first comprehensive examination of this subject. It looks at the location, scope, and significance of the right to a judicial determination of the legality of one's detention as guaranteed by international and regional human rights instruments. First, it examines the history of habeas corpus and its place in human rights treaties, providing a useful resource for understanding the status and application of this internationally-protected right. The book continues by identifying and analyzing the primary challenges to habeas corpus, in particular its applicability during armed conflict, the possibility of derogation, and its extraterritorial application and procedural shortcomings. The book next addresses the significance of habeas corpus guarantees not just in protecting personal liberty, but in promoting the international rule of law by serving as a unique check on executive action. Finally, it offers suggestions on how this right might be strengthened.